2012
DOI: 10.1523/jneurosci.3985-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Amplitude and Timing of the BOLD Signal Reflects the Relationship between Local Field Potential Power at Different Frequencies

Abstract: There is growing evidence that several components of the mass neural activity contributing to the local field potential (LFP) can be partly separated by decomposing the LFP into nonoverlapping frequency bands. Although the blood oxygen level-dependent (BOLD) signal has been found to correlate preferentially with specific frequency bands of the LFP, it is still unclear whether the BOLD signal relates to the activity expressed by each LFP band independently of the others or if, instead, it also reflects specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
290
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 324 publications
(332 citation statements)
references
References 65 publications
(95 reference statements)
34
290
4
Order By: Relevance
“…We report differential contributions of individual EEG frequency bands to the fMRI signal, as depicted by region-specific spectral profiles. Previous studies have suggested that local and network fMRI signals are associated with a mixture of electrophysiological processes underlying dynamic neuronal interactions at different temporal and spatial scales, which may be characterized by a varying interplay of distinct frequency components (Mantini et al 2007;Goense and Logothetis 2008;Scheeringa et al 2011;Magri et al 2012). Thus, the observed spectral profile may serve as an index, or "fingerprint" ) that reflects the relative contributions of the various distinct networks that contribute to a region's activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We report differential contributions of individual EEG frequency bands to the fMRI signal, as depicted by region-specific spectral profiles. Previous studies have suggested that local and network fMRI signals are associated with a mixture of electrophysiological processes underlying dynamic neuronal interactions at different temporal and spatial scales, which may be characterized by a varying interplay of distinct frequency components (Mantini et al 2007;Goense and Logothetis 2008;Scheeringa et al 2011;Magri et al 2012). Thus, the observed spectral profile may serve as an index, or "fingerprint" ) that reflects the relative contributions of the various distinct networks that contribute to a region's activity.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this spectral range is accessible with EEG. Over a much longer time scale in the order of several seconds to tens of seconds, network activity presents as comodulations in the power envelop of specific spectral bands, to which neuronal oscillations contribute (Leopold et al 2003;Lu et al 2007;Nir et al 2008) and which have an fMRI correlate (Magri et al 2012). Although extensive efforts have been made to characterize these "fast" and "slow" network interactions separately, their relationship has rarely been studied and remains largely unknown.…”
Section: Spectral Signature Of Interregional Functional Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological source of BOLD signal has been well‐characterized by previous research and it is known to reflect changes in blood oxygenation that occur following coherent neuronal activity (Baumann et al., 2010; Logothetis, Pauls, Augath, Trinath, & Oeltermann, 2001; Magri, Schridde, Murayama, Panzeri, & Logothetis, 2012). However, a major limitation of BOLD imaging is that changes in blood flow are not a direct measurement of neural activity, likely requiring the involvement of astrocyte‐mediated signaling pathways (Rossi, 2006; Takano et al., 2006) and occurring approximately 4–6 s after neuronal activity (Baumann et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…2010; Magri et al. 2012). The high‐frequency gamma range has been associated with excitatory and inhibitory synaptic activity (Brunel and Wang 2003) and is believed to represent synchronous activity from large neural networks (Jensen et al.…”
Section: Discussionmentioning
confidence: 99%